Acute macular neuroretinopathy: clinical cases - Zhazybaev, Ruslan S.; Sorokin, Evgenii L.; Zhirov, Arkadiy L.; Danilov, Oleg V. (Kliničeskaâ praktika, 2025)
BACKGROUND: Acute macular neuroretinopathy is a rare disease of the central retinal zone. CLINICAL CASES DESCRIPTION: The first clinical case represents a male patient aged 47 years with the complaints of a decreased vision acuity and developing a spot in the vision fields of the left eye. He was treated at the ophthalmology clinic due to acute central serous chorioretinopathy with no effect. At the moment of examination, his vision acuity in the left eye was 1.0, with the anterior segment showing no abnormalities, the ophthalmoscopy has not revealed any changes. According to the data from the optical coherence tomography of the macular zone, the findings included the changes in the reflectivity at the level of the external plexiform and the external nuclear layers. The diagnosis set was «Acute macular neuroretinopathy in the left eye», the recommendations included dynamic follow-up. The second description is a case of female patient aged 39 years, undergoing dynamic checkups due to the operated squamous carcinoma in the lower orbital wall on the right side and in the maxilla, s/p radiation therapy. The patient had no vision-related complaints, but the ophthalmoscopy of the right eye (at the macular zone para- and perifoveally) has revealed three «cotton-wool-like» exudates. According to the data from the optical coherence tomography, in the right eye, there were foci of hyperreflectivity at the level of the neural layer of retinal fibers along with the corresponding «cotton-wool-like» exudates, as well as juxtafoveally at the level of the external nuclear layer, which is characteristic for acute macular neuroretinopathy. CONCLUSION: The first clinical case shows the importance of multimodal diagnostics in cases of complaints of a decreased vision acuity and spots in the vision fields, despite the high acuity of central vision. The second clinical case demonstrates that radiation therapy, conducted in the areas adjacent to the eyeball, is capable of resulting in an impaired circulation in the capillary plexuses of the retina, including the superficial vascular complex and in the deep capillary plexus with the development of ischemic retinal manifestations.